Desarrollo y caracterización de películas delgadas depositadas por la técnica de electrodeposición de la capa de cobre/antimonio en el compuesto ternario CuSbS2 de manera secuencial (2020)
In this degree project, thin films of the ternary compound CuSbS2 were developed, which have a calcostibite structure deposited sequentially. In this way, laboratory-scale studies were carried out on the parameters of each solution used to make these films, which are divided into two layers of different material and were deposited by the electrodeposition technique sequentially with two electrodes, the first layer copper and the second antimony in a substrate / Mo system, the bilayer was subsequently sulfurized obtaining the copper sulfide and antimony compound. For this, different variables such as voltage, concentration, temperature and pulses were evaluated, according to the compound around the growth of the film, its uniformity and its composition. To perform the bilayer, acid solutions with fixed potential were prepared with the aid of the pulsating current technique (PDC).